Final score [videorecording (DVD)] - Bautista, David, 1969-; Stevenson, Ray, 1964-; Dinu, Alexandra, 1981- (Lionsgate, 2018)
After deadly terrorists abduct his niece at a soccer match, an ex-soldier with lethal fighting skills wages a one-man war to save her and prevent mass destruction.